2019
DOI: 10.1177/1753193419866117
|View full text |Cite
|
Sign up to set email alerts
|

Re-motion total wrist arthroplasty: 39 non-rheumatoid cases with a mean follow-up of 7 years

Abstract: We evaluated the outcomes of the Re-motion total wrist arthroplasty in 39 non-rheumatoid patients. The mean follow-up was 7 years (range 3–12). Postoperative wrist flexion-extension and radial-ulnar deviation as well as the scores of the Disability of Arm Shoulder and Hand questionnaire and the visual analogue scale pain scores improved significantly. Complications occurred in 13 wrists, five of which required further surgery. The most frequent complication was impingement between the scaphoid and the radial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
1
21
0
2
Order By: Relevance
“…Recently, some authors have extended the range of indications for TWA to non-rheumatoid conditions and compared their results to rheumatoid arthritis [ 4 , 5 , 6 ]. The present study and the previously published study [ 7 ] are the first ones to solely present outcomes of non-rheumatoid patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some authors have extended the range of indications for TWA to non-rheumatoid conditions and compared their results to rheumatoid arthritis [ 4 , 5 , 6 ]. The present study and the previously published study [ 7 ] are the first ones to solely present outcomes of non-rheumatoid patients.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review identified all patients who underwent TWA between July 2007 and February 2018 at a single institution. Compared to our previous study [ 7 ], we have extended the review period to identify all patients with a theoretical follow-up period of a minimum of 24 months. In this period, two level IV surgeons [ 8 ] performed TWA using CCR according to the manufacturer‘s surgical technique [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebenfalls für die Universal2Prothese (Integra Life Sciences) haben Brinkhorst et al 2017 [33] [39] operierten mit diesem Implantat dagegen ausschließlich posttraumatische Fälle (n = 39) und fanden nach durchschnittlich 7 Jahren immerhin 13 Komplika tionen von denen aber in 5 Fällen ein Impingement zwischen der radialen Prothesenkomponente und dem Skaphoid, welches durch ein ausreichendes intraoperatives skaphoidales Trimming hätte vermieden werden können. Immerhin musste nach 7 Jahren nur eine von 39 Prothesen gewechselt werden.…”
Section: Hemiprothesenunclassified
“…Total wrist arthroplasty (TWA) has a history as long as total knee and hip joint replacements 1 ; however, it has not demonstrated the same high survival rates 2‐4 . Although current TWA designs 5‐8 have improved over the past decade and have started to become a reliable option for some patients, 6 high complication rates are still a major issue 9‐11 . While the reasons for the complications following a TWA are debated, studies evaluating total joint replacements of the knee, shoulder, spine, and hip have shown that kinematic differences between the healthy and replaced joint motion can lead to implant and bone‐implant interface failures 12‐16 .…”
Section: Introductionmentioning
confidence: 99%